Conduction studies of phrenic nerve in healthy children - V. B. Voitenkov; V. N. Komantsev; N. V. Skripchenko; E. V. Ekusheva; A. V. Klimkin; A. I. Aksenova (Нервно-мышечные болезни, 2018)
Background. Unlike parameters of phrenic nerve conduction in healthy adults characterized by stability, in children variations with age are observed. The objective is to investigate the M-wave latency and amplitude in electroneurographic (ENG) examination of the phrenic nerve in healthy children of different ages for development of a normative database of neurophysiological data.Materials and methods. 48 healthy children (28 girls and 20 boys) were examined. Mean age was 9.19 ± 5.43 years (1–18 years). ENG examination of the phrenic nerve was performed with the modified standard procedure of stimulation at the level of the outer margin of the lower third of the sternocleidomastoid muscle with registration of M-wave from standard diaphragm point and parallel registration of the muscle activity from m.deltoideus and m.serratus anterior.Results. Mean values of the M-response latency were 5.64 ± 1.25 ms, amplitude – 0.66 ± 0.34 mV. For age-differentiated subgroups 1–2 years (n = 7), 3–5 years (n = 9), 6–12 years (n = 15), and 13–18 years (n = 17), the latency was 4.96 ± 1.94; 5.01 ± 1.13; 5.42 ± 0.84, and 6.44 ± 1.43 ms, respectively; the amplitude was 1.01 ± 0.37; 0.87 ± 0.31; 0.61 ± 0.24, and 0.45 ± 0.21 mV, respectively. The M-response amplitude values in children aged 1–2 years significantly differed from the values in children aged 6–12 and 13–18 years.Conclusion. ENG examination of the phrenic nerve is a technically uncomplicated procedure, and the obtained data is easy to interpret. During phrenic nerve ENG in children, it is necessary to take age variability of the M-wave latency and amplitude into account. The M-wave amplitude in healthy toddlers (1–2 years old) was significantly lower than in children aged 6–18 years.